Influence Green Bean Extract in Increasing Hemoglobin (Hb) Levels in Trimester II Pregnant Motherat Pratama Clinic of bunda Tessa Dusun 1A Sidourip Sub-District Beringin Deli Serdang Regency in 2023 - Wahara, Willhelmina; Nababan, Novrida (PT Inovasi Pratama Internasional, 2024)
Introduction: Pregnant women with anemia are still many in Indonesia, including in North Sumatra which reached 39%. Pregnancy is very susceptible to anemia that can cause bleeding in pregnant women. Purpose: The purpose of this study was find out the influence Green Bean extract in increasing Hemoglobin Levels in Trimester II Pregnant Women in Pratama Clinic of Bunda Tessa Dusun IA Sidourip Subdistrict Beringin District Deli Serdang in 2023. Method: Types of Quasy Experiment with the design of One Group Pretest Posttest. The population was 20 people. Sampling technique with purposive sampling was a selection of samples based on certain characteristics as many as 10 people, the statistic test used wilcoxon test. Result: Based on the result showed that the data obtained was pre-test minimum value of 8.4 maximum 11.9 while post-test minimum 10.8 maximum13.7. From the results of statistical tests thatwas with wilcoxon test known value P-value= .11 <. 05. Conclusion: The ability in this study is the effect of green bean extract on increasinghemoglobin levels in trimester II pregnant women in Pratama Clinic of Bunda Tessa Dusun IA Sidourip Subdistrict Beringin District Deli Serdang in 2023. It is suggested to be an evaluation and reference material for health workers to be applied and can inform pregnant women who have anemia in a natural way that is by consuming green bean juice as much as 200 ml.